2023
DOI: 10.1186/s12931-023-02575-3
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating interstitial lung diseases from other respiratory diseases using electronic nose technology

Iris G. van der Sar,
Marlies S. Wijsenbeek,
Gert-Jan Braunstahl
et al.

Abstract: Introduction Interstitial lung disease (ILD) may be difficult to distinguish from other respiratory diseases due to overlapping clinical presentation. Recognition of ILD is often late, causing delay which has been associated with worse clinical outcome. Electronic nose (eNose) sensor technology profiles volatile organic compounds in exhaled breath and has potential to detect ILD non-invasively. We assessed the accuracy of differentiating breath profiles of patients with ILD from patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Alterations in urinary VOCs have been linked to pathological conditions like tumors and infections. Various research has demonstrated the eNose ability to detect these changes in urine, successfully identifying various human neoplasia, such as prostate ( 10 , 14 ), bladder ( 15 ), kidney ( 16 ), breast ( 17 ), lung ( 18 ) and colorectal ( 19 ) cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in urinary VOCs have been linked to pathological conditions like tumors and infections. Various research has demonstrated the eNose ability to detect these changes in urine, successfully identifying various human neoplasia, such as prostate ( 10 , 14 ), bladder ( 15 ), kidney ( 16 ), breast ( 17 ), lung ( 18 ) and colorectal ( 19 ) cancers.…”
Section: Introductionmentioning
confidence: 99%